An enhanced transcutaneous delivery of botulinum toxin for the treatment of Hailey–Hailey disease. Issue 1 (27th December 2019) - Bar‐Ilan, Efrat; Koren, Amir; Shehadeh, Wasim; Mashiah, Jacob; Sprecher, Eli; Artzi, Ofir
Abstract: Successful treatment of Hailey–Hailey disease with intradermal botulinum toxin injections has been previously reported. The main disadvantages of this treatment are the excruciating pain and the risk of infections due to the numerous injections. We sought to evaluate the clinical effectiveness and safety profile of a novel approach using an energy‐based device (Tixel, Novoxel, and Israel), followed by the topical application of botulinum toxin Type A for the treatment of Hailey–Hailey disease. A retrospective study of all cases of histologically diagnosed cases of Hailey‐Hailey disease treated with Tixel device followed by topical application of botulinum toxin between 2018 and 2019 was performed. Epidemiologic, clinical, and treatment data, including effectiveness score and safety, were reviewed. The study included eight patients, of whom seven patients (87.5%) showed good or partial response. No systemic or local adverse effects were reported. There was no difference in effectivity between different body areas. Response to treatment ranged between patients with an average duration of 7.125 months after the second treatment. Tixel treatment followed by topical application of botulinum toxin can be considered in the treatment of Hailey–Hailey disease. This approach is less invasive, less painful, and yet effective as well as safe.